Pemberian Penguatan (Reinforcement) Terhadap Prestasi Belajar PAK Siswa - Pasaribu, Resmita (STT Injili Indonesia Medan, 2021)
Abstract: The purpose of this study is to state that the provision of reinforcement (reinforcement) can increase interest and learning achievement of Christian Religious Education in schools. This study uses a descriptive qualitative approach to explain the reinforcement skills given by Christian Religious Education teachers in the learning process which can cause students to be encouraged to make learning efforts and develop learning outcomes. Teachers who apply reinforcement are teachers who give something fun to students who do something positive. Reinforcement provided by the teacher and strengthens self-esteem and self-confidence of students. A student definitely needs reinforcement because the reinforcement given by the teacher is an encouragement for students to increase learning motivation. PAK teachers must have teaching skills, especially the skills to provide reinforcement so that teachers are able to encourage students' enthusiasm for learning in achieving learning achievement. For students in achieving achievement, a teacher must also motivate students to be more active in learning, master the PAK method well so that it can increase student interest and achievement in school.Keywords: giving reinforcement, learning achievementÂ Â Abstrak:Tujuan penelitian ini adalah untuk menyatakan bahwa pemberian penguatan (reinforcement) dapat meningkatkan minat dan prestasi belajar Pendidikan Agama Kristen di sekolah. Penelitian ini menggunakan pendekatan kualitatif deskriptif untuk menjelaskan tentang keterampilan pemberian penguatan yang diberikan guru Pendidikan Agama Kristen dalam proses belajar yang dapat mengakibatkan siswa terdorong untuk melakukan usaha belajar serta mengembangkan hasil belajar. Guru yang menerapkan pemberian penguatan adalah guru yang memberikan sesuatu hal menyenangkan kepada siswa yang melakukan sesuatu perbuatan positif. Penguatan yang diberikan oleh guru dan memperkuat harga diri dan rasa percaya diri siswa. Seorang siswa pasti membutuhkan penguatan sebab penguatan yang diberikan guru merupakan dorongan siswa meningkatkan motivasi belajar. Guru PAK harus memiliki keterampilan mengajar khususnya keterampilan memberi penguatan supaya guru mampu mendorong semangat belajar siswa dalam mencapai prestasi belajar. Bagi siswa dalam mencapai prestasi, seorang guru juga harus memberi motivasi kepada siswa agar semakin giat dalam belajar, menguasai metode PAK dengan baik sehingga dapat meningkatkan minat dan prestasi belajar siswa di sekolah.Kata Kunci: pemberian penguatan (reinforcement), prestasi belajar